COMPARATIVE ANALYSIS OF LANDFORM UNITS CORRESPONDING TO THE THIRD TAXON IN DIFFERENT GEOMORPHOLOGICAL MAPPINGS IN THE STATE OF PARANÁ - Silveira, Claudinei Taborda da; Michael Pinheiro Silveira, Ricardo (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
The growing debate on geomorphological cartography in Brazil has led to the formulation of the Brazilian Relief Classification System (SBCR), currently under development through collaboration between the community of geomorphologists, represented by UGB, IBGE and the Geological Survey of Brazil (SGB/CPRM). The SBCR is based on the hierarchical organization of taxa for geomorphological representation. In this sense, this paper aims to contribute to the debate through the comparative analysis of the landform units corresponding to the 3rd taxon of two geomorphological mapping works covering the state of Paraná, both at a scale of 1:250,000: the geomorphological units of the Environmental Information and Database (BDiA) of IBGE and the morphosculptural subunits of the Geomorphological Mapping of Paraná. The comparison revealed that the first identified 16 units, while the second mapped 50. Only four units share the same name in both mappings (Coastal Plain, Serra do Mar, Curitiba and Apucarana Plateaus), but with limited spatial correspondence (96%, 55%, 33% and 18%, respectively). The mapping of Paraná highlighted the predominance of plateaus in the state, designating 43 of the 50 units as "plateau", without resorting to the terminologies of “patamares”, depressions and “serras” used in the BDiA/IBGE. The geomorphological units of the BDiA are excessively generalized in comparison to the geomorphological mapping of Paraná.